Duodenal Wedge Resection for Large Gastrointestinal Stromal Tumour Presenting with Life-Threatening Haemorrhage. (24th March 2013) - Shaw, Alexander; Jeffery, John; Dias, Laura; Nazir, Sarfraz
Abstract : Background . Duodenal gastrointestinal stromal tumours (GISTs) are an uncommon malignancy of the gastrointestinal (GI) tract. We present a case of life-threatening haemorrhage caused by a large ulcerating duodenal GIST arising from the third part of the duodenum managed by a limited duodenal wedge resection. Case Presentation . A 61-year-old patient presented with acute life-threatening gastrointestinal bleeding. After oesophagogastroduodenoscopy failed to demonstrate the source of bleeding, a 5 cm ulcerating exophytic mass originating from the third part of the duodenum was identified at laparotomy. A successful limited wedge resection of the tumour mass was performed. Histopathology subsequently confirmed a duodenal GIST. The patient remained well at 12-month followup with no evidence of local recurrence or metastatic spread. Conclusion . Duodenal GISTs can present with life-threatening upper GI haemorrhage. In the context of acute haemorrhage, even relatively large duodenal GISTs can be treated by limited wedge resection. This is a preferable alternative to duodenopancreatectomy with lower morbidity and mortality but comparable oncological outcome.